The Impact of Kidnapping on Agriculture Activities in Ukum Local Government Area, Benue State, Nigeria - Rosemary Onchi Daniel; Nyikyaa Tersur Kelvin (International Journal of Humanities, Education, and Social Sciences, 2026)
Kidnapping has emerged as a major security and development challenge in Nigeria, with particularly severe consequences for agrarian communities whose livelihoods depend on agriculture. In Ukum Local Government Area of Benue State, recurrent abductions have disrupted farming activities, obstructed trade routes, displaced farmers, reduced labor availability, and discouraged investment, thereby intensifying food insecurity and economic hardship. This study aimed to examine the impact of kidnapping on agricultural activities in Ukum LGA. The study was anchored in Anomie theory, as developed by Émile Durkheim and refined by Robert K. Merton, to explain how structural strain, blocked opportunities, and weakened social norms may contribute to criminal behavior, including kidnapping. A cross-sectional survey design was adopted. The study population comprised residents of Ukum LGA, and a sample of 400 respondents was determined using Taro Yamane’s formula. Respondents were randomly selected across thirteen wards, while data were collected through structured questionnaires and interviews with twelve key informants. The data were analyzed using descriptive statistics, specifically frequencies and percentages. The findings revealed that kidnapping has significantly disrupted agricultural activities in the study area, resulting in food insecurity, farmer displacement, blocked trade routes, and reduced agricultural investment. The study concludes that kidnapping undermines agricultural production, rural livelihoods, and food security in Ukum LGA. These findings highlight the need for strengthened rural security, targeted support for displaced farmers through access to farmland and agricultural inputs, investment incentives for agricultural recovery, and community awareness initiatives to mitigate kidnapping risks and restore agricultural productivity.